LANGUAGE VARIETY OF HEALTH CARE SERVICES AT PUSKESAMAS BANTARAN KABUPATEN PROBOLINGGO - Amalia, Nur Ismi; Mulyono, Sugeng Edy; Amalia, Rasyidah Nur; Hidayati, Nuril (JURNAL LITERASI, 2024)
: This study analyzes the language variety used by nurses and patients of health care services at Puskesmas Bantaran Kabupaten Probolinggo. Language variety refers to variants of language caused by the speakers’ different backgrounds. Puskesmas Bantaran is a referral puskesmas with medical personnel and patients from different backgrounds and it causes challenges in the communication process during health care services. The theory used to analyze the data in this study is the theory from Janet Holmes (2013). Language variety is divided into two aspects namely, language variety of speakers and language variety of the use. This research is important to improve the effectiveness of communication between medical personnel and patients. This research aims to describe the types of language variety used by a nurse to patients of health care services at Puskesmas Bantaran Kabupaten Probolinggo. The method used is descriptive-qualitative with data collection methods through observation, recording, transcribing, and interviews. The data source consists of all dialogs of conversational interaction between a nurse and patients of health care services containing language variety. The data were analyzed from 24 conversations, resulting in 101 language variety. The results of the analysis show that there are two language variety of health care services in the interaction between a nurse and patients, namely language variety of speakers and language variety of the use. The language variety of speakers has 87 data which is divided into five types, namely social status and ethnicity (51 data), gender (10 data), age (24 data), and social network (2 data). The language variety of the use or register of health has 14 data. These findings reflect the social interaction between a nurse and patients of health care services.